Quality of financial reporting and the level of compliance with SAS: A case study of Islamic banking in Indonesia - Iryani, Lia Dahlia (Proceeding International Conference on Accounting and Finance, 2024)
The objective of this paper is to examine the effect of the level of compliance of financing accounting with SAS (Sharia Accounting Standards) on the quality of financial reporting, and the quality of the maqasid (objective) Sharia-based performance of Islamic banks in Indonesia. Understanding the basic principles of the accounting standards of Islamic banking has become increasingly important among most Sharia scholars and researchers in the implementation of accounting standards for Islamic Banking Industry (IBs). Currently, IBs are one of the fastest growing sectors locally and globally. The level of compliance of financing accounting with SAS, the quality of financial reporting, and maqasid Sharia-based performance were measured using questionnaires distributed to 34 directors and heads of Islamic banks. The study model was analyzed using partial least squares structural equation modelling (PLS-SEM). The study found that the level of financing accounting compliance with SAS had positive impacts in improving the quality of financial reporting and maqasid Sharia-based performance. Therefore, Islamic banks in Indonesia have fully adopted SAS. The limited number of indicators of financing accounting practices in the study mean that fewer comprehensive financing accounting practices are illustrated. Further studies could add other relevant financing accounting practices, as described by the IAI (Indonesian Accounting Association), in order to provide a more comprehensive overview. The study contributes to the accounting of Islamic banks by improving the conceptual framework of SAS, which could benefit future research. The paper supplements the limited number of empirical studies on financing accounting practices in the Islamic banking industry.